Sistem Penjadwalan dan Presensi Adaptif untuk Optimalisasi Manajemen Operasional di Rumah Sakit - Sari, Gita Mailand; Widiartha, Ida Bagus Ketut; Rosika, Herliana (Universitas Hamzanwadi, 2025)
Mataram University Hospital faces problems in managing work schedules that are still manual using excel and are not integrated with the attendance system. This has an impact on operational management in hospitals that are less than optimal. This research aims to produce an adaptive scheduling and attendance system display that is integrated with the registration module in the Hospital Management Information System (HMIS). The method used to build the system is the User Centered Design (UCD) Method integrated with the Extreme Programming (XP) Method, which includes the stages of user identification, identification of user needs, design and testing iteratively. Data was collected through observation and interviews with the hospital and analyzed qualitatively. Our findings resulted in the appearance of a scheduling and attendance system that aims to optimize operational management in hospitals. Testing the system interface using Usability Testing Method, System Usability Scale (SUS) and User Experience Questionnaire (UEQ) to test the functionality and user experience conducted to 30 respondents consisting of staff and doctors. The SUS test results obtained a score of 76.41 and the “Good” category for all aspects of the UEQ test. Overall, the system has a good level of usability and user experience. This system successfully optimizes operational management in hospitals.